2011
DOI: 10.1111/j.1471-0528.2011.03088.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of well women seeking labial reduction surgery: a prospective study

Abstract: Objective To assess clinical characteristics and expectations in well women requesting elective labial reduction surgery.Design Prospective study of women attending an outpatient gynaecology clinic.Setting General gynaecology clinic at a Central London teaching hospital.Sample Women requesting labial reduction surgery and referred by their general practitioner.Methods The labia minora width and length were measured for all participants for comparison with published normal values. The presenting complaint was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
2
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 7 publications
3
72
2
5
Order By: Relevance
“…Although much of this has been retrospective, recent studies have been prospective. [17][18][19][20][21] A small pilot study published in 2011 17 found significant short term (6-month) resolution of apparent body dysmorphic complaints noted at study entry. Veale et al noted similar findings at 3 months postoperative, using a different testing instrument.…”
mentioning
confidence: 99%
“…Although much of this has been retrospective, recent studies have been prospective. [17][18][19][20][21] A small pilot study published in 2011 17 found significant short term (6-month) resolution of apparent body dysmorphic complaints noted at study entry. Veale et al noted similar findings at 3 months postoperative, using a different testing instrument.…”
mentioning
confidence: 99%
“…This is consistent with findings in the Netherlands from the survey by Koning et al (2009), which found that most women sought information about labiaplasty through the media. Social-cultural factors such as the ease of access to pornography over the Internet and comparisons with porn actresses have been suggested (Crouch, Deans, Michala, Liao, & Creighton, 2011); although only 12% of the women in their sample reported viewing pornography. An increase in television programmes, such as 'Embarrassing Bodies' in the UK, and coverage in women's magazines normalises and legitimises labiaplasty and may fuel the demand.…”
Section: Discussionmentioning
confidence: 99%
“…(5,57) Another study investigating women's motivation for undertaking labioplasty reported that, in the clinic where the study was undertaken, labia reduction surgery is only offered to women (over 18 years) with either or both of the following: labial width >50 mm or labial asymmetry with > 30 mm difference. (70) Across the studies, complaints of discomfort or pain with intercourse, clothing or exercise and repeated infection were reported with labia length < 3 cm (7) and < 4 cm (56) , indicating high variation of women's experiences in relation to symptoms and labial hypertrophy.…”
Section: Assessment Of Hypertrophy Of the Labia Minoramentioning
confidence: 99%
“… functional anatomical discomfort and pain (12,56,70) (e.g. superficial dyspareunia, pain and/or discomfort during exercise and whilst wearing tight clothing);  psychosocial factors (14) (e.g.…”
Section: Clinical Indications For Vulvoplasty and Labioplastymentioning
confidence: 99%
See 1 more Smart Citation